Vulnerability in health and social capital: a qualitative analysis by levels of marginalization in Mexico - Oscar A. Martínez-Martínez; Anidelys Rodríguez-Brito (BMC, 2020)
Abstract Background Social capital is employed as an asset when there is a lack of an efficient health-care system. However, this relationship is not homogeneous and can differ according to the characteristics of individuals and their context. In this paper, we aim to analyze the role of social capital in the solution of healthcare problems among individuals with different levels of marginalization and unequal access to health services. Methods This qualitative study examines the role of social capital in the demand for healthcare among Mexican individuals with different levels of marginalization. The research draws data from semi-structured interviews (N = 247) that were collected in four Mexican states with different social welfare benefits: Mexico City, Tamaulipas, the State of Mexico, and Oaxaca. The interviewees were selected using the snowball method and other eligibility criteria such as education, age, and gender. Results Findings suggest that social capital is a relevant factor in solving healthcare problems, depending on the level of marginalization. The role of social capital can be explained by the precariousness of medical service delivery, the poor health infrastructure, and the difficult access to health care in Mexico. Networks are the main resource to deal with health related issues, food, medicine, and out-of-the-pocket medical expenses in contexts of high levels of marginalization. In the middle level of marginalization, networks also help in raising funds for more-specialized medical services and higher quality hospitals. In the least-marginalized levels, social capital is used as companionship for sick individuals, while support networks act as emotional relief. At this level, most individuals have private health insurance, and many of them have major medical healthcare coverage. Conclusions Participants reported low levels of trust in the health care system because of the poor infrastructure and quality of medical service delivery. Although the main criticism is focused on public healthcare institutions, there is a lack of trust in private medical services as well. These facts are related to the access and quality of medical service delivery and turn social capital into a significant asset. Despite that social bonds or links are valuable resources that individuals can use to solve healthcare related issues, the use of social capital is not homogenous. Indeed, it can be influenced by several factors that were represented in this study through the municipal marginalization index.